HUBUNGAN PENDAMPINGAN SUAMI DALAM PERSALINAN DENGAN KEMAJUAN PERSALINAN KALA I FASE AKTIF DI RB. BUNDA PUJA TEMBILAHAN - Dewi Erlina Asrita Sari; Nurul Indah Sari; Nanda Putri Zulaikha (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2020)
The labor is the process by which thet baby, placenta and membranes come out of the mother's uterus. Childbirth companion is a person who can do much to be able to help the mother during labor. Based on the preliminary survey, the number of mothers in RB. Bunda Puja in 2017 as many as 282 normal maternity mothers. Observation results for 1 week from 8 maternity mothers there were 6 people accompanied and 2 people who were not accompanied by their husbands or families, from 6 people who were accompanied by the birth process faster than 2 people who were not accompanied so they had a long labor. The purpose of this study was to determine the relationship of husband's assistance in labor with the progress of active phase I labor in RB. Bunda Puja Tembilahan in 2017. This type of research is analytic with Case Control design conducted on March 8 to March 10, 2018 on RB. Bunda Puja Tembilahan. The number of cases is 65 with a total sampling technique and a control group of 65 with a systematic sampling random sampling technique. Data collection tools use the Checklist sheet. Analysis of the data used is univariate and bivariate analysis with chi square test. The results of this study showed that the number of women who were accompanied by their husbands had a fast delivery as many as 43 people (66.2%) and mothers who were not accompanied by their husbands experienced a slow delivery of 42 people (64.6%). The results of the analysis were obtained (p-value <0.05), it means that there was a relationship between the husband's assistance in labor and the progress of labor in the first phase of active phase. The medics is expected to motivate the childbirth companion in supporting the maternity mother